Open Partial Nephrectomy: Results from an 8 Year Study - Goonewardene S; Shafik A; Chen TF; Makar A (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Introduction: Nephron sparing surgery is an effective treatment for RCC. Oncological outcome is equivalent to radical nephrectomy, with the added functional advantage. It is underutilized, especially in tumours in anatomically challenging positions like central and hilar positions. Methods: We analyzed the hospital case notes and electronic records of 90 consecutive cases of partial nephrectomies, done at our hospital over the last 8 years. We collected data on the tumours  number, size, position (upper zone, central/hilar and lower zone), histology, margin status, operative time, ischemic time, peri-operative complications, length of stay and recurrences so far. We analysed these data according to tumour site (hilar/central vs. polar). Results: 43% of tumours were in the middle zone, 32% lower and 25% upper zone. 81% had elective and 19% imperative indication for nephron sparing surgery. 15% had bilateral tumours. Cold ischemia was used in 40% of the time (20.7 min), warm ischemia in 17% (7.2 min) and no arterial clamping in 43% of the time. The collecting system was opened in 79% of cases. Average operative time was 130 min and length of stay 7.2 days. Complications included, chest infection (4.5%), urinary retention (3.4%), ARF(3.4%), re-operation(2.2%), urinary leak(2.2%) and incisional hernia(5.6%). To date there has been no recurrences or metastatic disease. There was no difference in these results between central/hilar tumours as opposed to upper and lower pole tumours. Conclusion(s): Although may be more technically challenging, nephron sparing surgery for central and hilar tumours is safe and effective.